Analyzing The Concept Of Operational Management at PT Campina Ice Cream Industry Company in Surabaya - Salomina Mebri; Magnus Alansisus Bebo; Aditya Dharma Ramadhan; Niken Bagas Firmansyah; Muhammad Yasin (SEAN Institute, 2023)
The development of the ice cream industry in Indonesia is increasingly competitive and varied. Consumers are not only children but extend to teenagers, adults and even parents. The improvement of the food and beverage industry is expected to become one of the leading sectors in encouraging the growth of the manufacturing industry and the Indonesian economy, The object of this research is PT Campina Ice Cream Industry Tbk is one of the leading fast moving consumer goods company categories in ice cream processing for 51 years which began in 1972. This study aims to analyze and describe the development of product quality, marketing strategies so that PT CAMPINA ICE CREAM can have achievements and improvements to company profitability. This study explain the Determine and analyze the company's financial performance in terms of profitability ratio. In the 2019-2020 period there was a decrease in profits, but in 2020-2021 the Campina Company increased sales based on innovations made.